1984
DOI: 10.1039/c39840000342
|View full text |Cite
|
Sign up to set email alerts
|

Visible light induced generation of hydrogen from H2S in mixed semiconductor dispersions; improved efficiency through inter-particle electron transfer

Abstract: Electron transfer from the conduction band of CdS to that of Ti02 particles occurs in alkaline suspensions containing SHions and is exploited to improve the performance of a system that decomposes H2S with visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
146
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(153 citation statements)
references
References 2 publications
(2 reference statements)
4
146
0
3
Order By: Relevance
“…For example, Reber and Rusek reported that platinized CdS (Pt-CdS) obtained by the photodeposition showed an enhanced hydrogen production rate of 300 mL/h at 1.5 wt% loading of Pt, 10 whereas Serpone et al observed that the enhancement of hydrogen production by platinization was almost negligible. 23 Although photoplatinization is expected to make a better contact at the Pt/CdS interface than physical mixing, the former was reportedly much less effective than the latter for the photocatalytic degradation of lactic acid. 32 The surface chemistry of CdS usually interferes with the photochemical reduction of Pt ion (Pt 4+ ) as follows:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Reber and Rusek reported that platinized CdS (Pt-CdS) obtained by the photodeposition showed an enhanced hydrogen production rate of 300 mL/h at 1.5 wt% loading of Pt, 10 whereas Serpone et al observed that the enhancement of hydrogen production by platinization was almost negligible. 23 Although photoplatinization is expected to make a better contact at the Pt/CdS interface than physical mixing, the former was reportedly much less effective than the latter for the photocatalytic degradation of lactic acid. 32 The surface chemistry of CdS usually interferes with the photochemical reduction of Pt ion (Pt 4+ ) as follows:…”
Section: Introductionmentioning
confidence: 99%
“…It enhanced hydrogen production compared to plain CdS, 25 but sometimes lowered the efficiency by 8 times. 23 We report a comparative study on the hybridization of CdS, TiO 2 , and Pt in terms of hydrogen production and photocurrent generation under visible light (l > 420 nm). It was found that changing the order of hybridization in the preparation step significantly altered the efficiency for both hydrogen production and photocurrent generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the electronic structure of nanocomposites based on metal oxides/sulphides have a profound influence on photocatalytic properties. The mixture of semiconductors based on TiO 2 /CdS has attracted attention because of their potential applications in the photodegradation of organic pollutants [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], the photoelectrolysis of water for hydrogen production [17][18][19][20], and the sensitization of solar cells [21,22]. Due to its wide band gap (3.0 for rutile and 3.2 eV for anatase), TiO 2 is able to absorb light in the UV range, which constitutes 3-5% of solar irradiation, while semiconductors with a narrower band gap, such as CdS, are effective under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Since UV light only accounts for about 5% of the solar radiation that reaches Earth's surface, the inability to utilize visible light limits the efficiency of solar photocatalytic hydrogen generation. Thus, different strategies have been adopted in order to improve this efficiency, including: i) varying the sizes of the nanoparticles, 10 ii) doping with metal/non-metal ions, 11 iii) coupling the titanium dioxide with low band gap semiconductors, 12 and iv) supporting metallic/metal oxide nanoparticles on the oxide surface to promote electron and hole transfer reactions at the TiO 2 /substrate interface. 13,14 In addition, it is desirable to produce TiO 2 structures composed mainly of the anatase phase, because it has higher catalytic activity than the rutile phase.…”
Section: Introductionmentioning
confidence: 99%